2023
DOI: 10.1021/acssensors.3c01321
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Selective Mechanism of NiO-TiO2 Heterojunction to H2 and CO

Shuai Nie,
Jing Li,
Lin Tao
et al.

Abstract: The construction of p-n heterojunctions has become a widely adopted strategy for achieving the selective detection of reducing gases, including H 2 and CO. Nevertheless, the elucidation of the gas selectivity mechanism at the nanoscale remains elusive. First-principle calculations provide an attractive avenue for comprehending the influence of coordination structures on gas-sensitive selectivity, thereby unveiling the structure−activity relationship of p-n heterojunction sites. In this study, we investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Initially, all gas molecules positioned 2.5 Å above the monolayer underwent structural optimization calculations to determine their equilibrium positions. Based on the positive correlation between the adsorption distance and energy, 50,51 the initial configurations following this criterion were selected, as illustrated in Fig. S15 and S16 †Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, all gas molecules positioned 2.5 Å above the monolayer underwent structural optimization calculations to determine their equilibrium positions. Based on the positive correlation between the adsorption distance and energy, 50,51 the initial configurations following this criterion were selected, as illustrated in Fig. S15 and S16 †Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Single-atom catalysts (SACs) with isolated transition metal (TM) atoms stabilized by carbon-based materials have attracted more and more attention due to their special electronic structure and platform utilization 12 and have become promising candidate materials in the nitrogen reduction reaction, 13 HER, 14–16 oxygen reduction reaction, 15,17 oxygen evolution reaction, 18,19 CO 2 RR, 20,21 and other reactions. 22 Previous studies have indicated that catalysts such as Mn, Mo, Ru, and Ti offer distinct advantages in the CO 2 RR compared to the HER, requiring lower overpotentials for the generation of intermediate products (*COOH or *OCHO). 23–29 Unfortunately, the stability of SACs is not satisfactory, 30 because when the bond of individual atoms to the carrier is weak, they tend to aggregate into nanoparticles, which inevitably affects their catalytic activity and further hinders their practical application.…”
Section: Introductionmentioning
confidence: 99%